Sport Fans as Consumers: An Approach to Sport Marketing - Coutinho da Silva, Edson; Luzzi Las Casas, Alexandre (British Journal of Marketing Studies, 2017)
This theoretical paper arises as a purpose of discussing the role play of fans as sport consumers on the marketing strategies, in professional sport clubs. This study is part of a project which will provide some other empirical papers which will use the fan perspective as one axis for analysing sport clubs in the São Paulo city, Brazil. In order to understand the sport fans as consumers, five topics were developed for contextualise them: (i) sport fans overview for explaining what fan means; (ii) loyalty and attendance for sport experiences in which the idea is comprising games as entertainments; (iii) sport fans as consumers in order to discuss what they love to consume; (iv) ‘new’ interactions between fans and teams, what does have been changed related to promotions? (v) and sport fans as foundations for revenues, what instruments sport clubs have used to get money from their fans? Therefore, this paper aims to highlight the point of view approached by literature to comprise the sport fans as consumers in sport club’s business.